Effect of phacoemulsification cataract surgery on intraocular pressure in early glaucoma: A prospective multi‐site study. (13th February 2020) - Qassim, Ayub; Walland, Mark J.; Landers, John; Awadalla, Mona; Nguyen, Thi; Loh, Jason; Schulz, Angela M.; Ridge, Bronwyn; Galanopoulos, Anna; Agar, Ashish; Hewitt, Alex W.; Graham, Stuart L.; et al.
Abstract: Importance: Cataract and primary open‐angle glaucoma (POAG) commonly co‐exist, and cataract surgery is thought to reduce intraocular pressure (IOP), the major modifiable risk factor of POAG. Background: Previous studies exploring the effect of cataract surgery on IOP are limited by retrospective design, lack of a control group, medication use and washout and loss to follow up. Design: Prospective, multicentre, matched case‐control Australian study. Participants: 171 eyes of 108 POAG patients who underwent cataract surgery, matched to 171 control eyes. Methods: Serial longitudinal IOP measurements were compared before and after cataract surgery, and relative to the controls. A mixed‐effect model was used for the longitudinal data. Main Outcome Measures: Change in IOP. Results: The mean follow‐up time was 4.8 (1.4) years. Cataract surgery reduced mean IOP by 2.22 mmHg (95% confidence interval: 1.93‐2.52 mmHg, P  < .001) with 59 eyes (34%) achieving at least 3 mmHg reduction. Compared to matched controls, the mean reduction in IOP was 1.75 mmHg (95% confidence interval 1.15‐2.33 mmHg; P  < .001). Higher preoperative IOP and being on fewer topical glaucoma medications preoperatively were strongly predictive of a larger IOP reduction in a multivariable model. Anterior chamber depth was not associated with IOP reduction. Eyes with preoperative IOP ≥24 mmHg had a mean IOP reduction of 4.03 mmHg with 81% experiencing at least 3 mmHg reduction. Sub‐analysis of medication naïve and pseudoexfoliation patients showed similar results. Conclusions and Relevance: Cataract surgery has a confirmed effect in reducing IOP in a "real world" setting of early glaucoma patients.